Seguimiento de Jesucristo en las comunidades parroquiales de la diócesis de Pereira. El desafío de permanecer y perseverar. Un análisis desde Marcos 4,1-20 (2021)
The realities of the new communities of New Evangelization and Christian initiation, lay and apostolic movements and groups, grouped under the Diocesan Pastoral Plan of New Evangelization, this year exceeds 25 years of existence in the diocese of Pereira, in fulfillment of the proposed challenge by Pope John Paul II to promote in Latin America a renewed effort of New Evangelization, after the fifth centenary of the encounter with the American continent. This has been a long and complex period, of sowing and replanting the Savior message of Jesus Christ, which has had moments of growth, and others, most of them, of stagnation and decay. In this article of theological reflection, it is intended to address the reality of what this evangelizing journey has been in the diocese of Pereira, very similar to other ecclesiastical circumscriptions in Colombia. Taking as a point of reference and reflection the Gospel of Mark, 4,1-20, the pericope of the sower as an illuminating text. Under a quali - quantitative methodology, and from the theological method of "seeing, judging and acting" to inquire with those who are part or have participated in this evangelizing process, what have been the main causes of desertion or abandonment of this continuous process that leads to the encounter with Christ and the constitution of communities as epicenters of this encounter. To show in the end, the verification of the absence of community sense that, together with the disfigurement of the meaning of being Christian, add causes for the dichotomy between daily life and religious praxis. At the end of the writing, some proposals for action are presented, which in the light of the evangelical pericope can reorient this evangelizing strategy, illuminating the great challenges of persevering and remaining in the follow-up.